Quantitative Visual Detection of Mercury Ions With Ratiometric Fluorescent Test Paper Sensor - Fan, Mimi; Pan, Zhihui; Wang, Chunjuan; Guo, Yang; Sun, Jingran; Liu, Mingzhu; Peng, Bo; Wu, Jin; Fang, Yanjun (Frontiers in Chemistry, 2022)
A novel ratiometric fluorescence probe based on nitrogen-doped blue carbon dots (NCDs) and red gold nanoclusters (Au NCs) for mercuric ion (Hg2+) has been prepared and characterized. A user friendly fluorescent test paper based sensor combined with smartphone was fabricated for rapid visual and quantitative detection. Hg2+ can specifically bind to Au+ on the surface of Au NCs, leading to the quench of red fluorescence while the fluorescence intensity of the NCDs with blue fluorescence remained unchanged as a internal standard signal. The implement of paper-based sensor address some common drawback in analytical process such as the detection time, analysis cost. In a further demonstration, a homemade detection device with smartphone was used to qualify the Hg2+. After adding different concentration of Hg2+, red, purple, and blue colors were obtained on the detection zones of the fluorescent test paper. The Android App Color Grab was used to identify the red, green and blue (RGB) values of fluorescent color. The rapid visual and quantitative detection of Hg2+ was accomplished with the detection limit of 2.7nM for fluorescence, 25nM for smartphone and 32 nM for paper strip. The developed multi-mode detection platform was successfully applied to the detection of mercury ions in water samples with acceptable recoveries. The NCDs and Au NCs probe facilitate the one-site environmental monitoring for Hg2+ with “naked-eye” and smartphone.